CONSERVATION AND DEVELOPMENT OF RESOURCES OF ASIATIC HARD CLAM IN COASTAL ALLUVIAL PLAIN OF GIAO THUY DISTRICT, NAM DINH PROVINCE - Thanh, Nguyen Xuan; Thung, Do Cong; Ve, Nguyen Dac; Nhan, Mai Dang; Cach, Nguyen Viet (Vietnam Journal of Marine Science and Technology, 2017)
The conservation of native species of hard clam (Meretrix meretrix) in Giao Thuy, Nam Dinh is now very necessary. Research results show that nature resources of hard clam have had the sign of decrease. The ecological conditions in coastal areas are unsuitable for growth and development clams, so they are pushed away from coast compared to the previous time. The biological characteristics of the native clam (Meretrix meretrix) such as spawning season, fecundity, the size at first sexual maturity, ecological threshold are inferior to those of invasive species (Meretrix lyrata). That is the basis for establishing conservation areas, zoning functional areas to conserve native species of clams and sustainable development of clam production in Giao Thuy, Nam Dinh. Based on the results of research on a scientific basis and reality, the orientation and measures of conservation and development of hard clam resources have been proposed with the establishment of the native clam conservation area of 3,090 ha, in which the core area of 420 ha is a place to store, protect resources of clams broodstock and clam seed; make up spawning grounds and natural seed beds; contribute to restoration, natural regeneration of the native clam resources.